Strategi Pencapaian Target Penyaluran Pembiayaan ULaMM pada PT Permodalan Nasional Madani Cabang Balikpapan - Muhammad Syaiful Anwar (Sekolah Pascasarjana Perbanas Jakarta, 2023)
The purpose of this study is to provide a summary of the strategies used and the suggested strategies to PT. Permodalan Nasional Madani (PT. PNM) Balikpapan Branch in marketing the distribution of Micro Capital Service Unit (ULaMM) financing during endemic and new normal conditions to increase the growth in the quantity and quality of UlaMM customers, including evaluating what factors are the causes of not achieving the financing distribution target ULaMM at PNM Balikpapan Branch. The analytical method used is the SWOT matrix, supported by quantitative analysis using the EFE, IFE, IE, and QSPM matrices. The data collection method in this study used the triangulation method of three techniques, namely observation, interviews and literature study. The results showed that the weight value for the Internal Factor Evaluation (IFE) matrix was 3.12 (strong position) and the External Factor Evaluation (EFE) was 2.95 (medium position). In the Internal External (IE) matrix, the strategy that must be carried out is a growth and build strategy, which consists of intensive strategies (market penetration, market development, product development) or integrative strategies (backward, forward and backward integration). horizontally). While the strategic priorities that can be applied in developing or increasing the distribution of this financing based on the QSPM matrix are building a network of cooperation, partnerships with various parties such as Banks, Government Agencies, BUMN Companies and Private Companies where one of which can be implemented is working on or capturing existing customers of fostered partners from Partnership and Community Development Program (PKBL) or Corporate Social Responsibility (CSR)